POLINOMIAL KROMATIK PADA GRAF KIPAS - Maulana, Nur Ridwan; Wijaya, Kristiana; Santoso, Kiswara Agung (Jurusan Matematika FMIPA Universitas Jember, 2018)
A chromatic polynomial of a graph G is a special function that describes the number of ways we can achieve a proper coloring on the vertices of G given k colors. In this paper, we determine a chromatic polynomial of a fan graph. Keywords: Proper coloring, chromatic polynomial, fan graph.